Selection of induction agents for safe and effective rapid sequence intubation⁠ - Amin Aljefri, Ahmed; Alqurashi, Abdulrahman S.; Alshahrani, Mubarak F.; Alshahrani, Saeed N.; Allehaimeed, Ibrahim S.; Alotaibi, Mohammed A.; Alarifi, Sitah T.; Aljohani, Ahmed A.; Khoj, Haitham A.; Samman, Hasan M.; Kaki, Waleed K. (International Journal Of Community Medicine And Public Health, 2025)
Rapid sequence intubation (RSI) is a critical procedure in emergency airway management, requiring rapid induction of unconsciousness and muscle relaxation to facilitate safe intubation. The choice of induction agent plays a pivotal role in optimizing outcomes, as each agent exhibits unique pharmacokinetic and pharmacodynamic profiles. Etomidate is frequently chosen for its hemodynamic stability, making it suitable for critically ill patients; however, concerns regarding adrenal suppression warrant caution in septic or prolonged critical illness cases. Ketamine is particularly advantageous in patients with reactive airway diseases or hypotension, owing to its bronchodilatory effects and ability to preserve respiratory drive, although its psychotomimetic side effects must be managed carefully. Propofol, characterized by its rapid onset and short duration, provides excellent intubating conditions but may cause significant hypotension, limiting its use in hemodynamically unstable patients. Thiopental, once widely used, is now less favored due to cardiovascular depression and prolonged recovery times. Patient-specific factors, including age, comorbidities, and clinical status, heavily influence agent selection. Pediatric and geriatric populations pose unique challenges, necessitating dose adjustments and close monitoring. Emerging agents like dexmedetomidine offer novel benefits such as sedation with preserved respiratory function, though slower onset limits its utility in emergency settings. The complexity of decision-making underscores the importance of understanding the nuances of each agent’s efficacy and safety. Despite advancements in pharmacological options, limitations in evidence, variability in patient responses, and resource constraints highlight the need for individualized approaches and adaptable guidelines. Further research is essential to bridge gaps in knowledge and establish standardized practices to enhance safety and effectiveness in RSI across diverse clinical scenarios.